PtCo ordered alloy material and preparation method and application thereof
By defect-treating carbon precursors to create porous carriers with intrinsic defects, the method synthesizes small-sized PtCo alloys that inhibit agglomeration and optimize electronic structure, addressing the challenges of high-cost and low-durability Pt/C catalysts and PtCo particle stability, achieving improved catalytic performance and reduced catalyst use.
Patent Information
- Application Number
- CN202411285025.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-13
- Publication Date
- 2024-12-17
AI Technical Summary
Existing Pt/C catalysts in PEMFCs require a high amount due to insufficient activity and poor durability, leading to high costs, while PtCo alloys face particle agglomeration and poor structural stability during high-temperature synthesis, making it difficult to achieve small-sized and ordered alloys with high utilization efficiency.
A method involving defect treatment of carbon precursors using active atmospheres like ammonia, carbon dioxide, or water vapor to create porous carriers with intrinsic defects, followed by microwave reaction and heat treatment to synthesize small-sized PtCo ordered alloys, inhibiting particle agglomeration and optimizing electronic structure for improved catalytic performance.
The method produces small-sized PtCo alloys with high precious metal utilization and enhanced catalytic activity and durability, reducing the amount of catalyst needed and improving the efficiency of oxygen reduction reaction.
Smart Images

Figure CN119144867A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a PtCo ordered alloy material and a preparation method and application thereof. Background Art
[0002] As a clean, efficient and renewable energy carrier, hydrogen energy has unique advantages and is considered an important part of the future energy system. Among them, proton exchange membrane fuel cells (PEMFCs) have attracted much attention and research as the most promising green and efficient power generation technology in the future. Among them, PEMFC cathodes usually require Pt / C catalysts to efficiently catalyze the oxygen reduction reaction (ORR). However, due to the insufficient activity and poor durability of Pt / C catalysts, a high amount of catalyst is generally required (>0.3mg·cm -2 Pt), which increases the cost of PEMFC devices. Therefore, it is particularly necessary to develop high-efficiency, low-cost and long-life ORR electrocatalysts.
[0003] At present, PtCo alloy catalysts are considered to be the representatives of the new generation of low-Pt catalysts, but the structure of its disordered solid solution makes it easy for Co atoms to be lost under working conditions, and the structural stability is poor, which affects the life of the battery. The current solution strategy is to transform disordered alloys into ordered PtCo alloys. This ordered PtCo alloy takes into account both high catalytic activity and structural stability and is regarded as the most promising ORR electrocatalyst. However, its synthesis usually requires high temperature to achieve ordered transformation, and high temperature conditions will inevitably cause particle agglomeration. The particle size is generally greater than 6nm, which seriously reduces the utilization efficiency of Pt atoms. Small particles have very high surface energy and are very easy to migrate and fuse at high temperatures. It is a very efficient particle size control method to reduce the surface energy of small particles through carrier engineering, thereby inhibiting the large-scale agglomeration of particles. Therefore, how to achieve the above-mentioned particle size control method and synthesize small-sized and ordered PtCo alloys has always been a scientific and technological problem in this field. Summary of the invention
[0004] The present invention is mainly to overcome the defects of the prior art in the process of preparing ordered PtCo alloys, that is, the particles are easy to agglomerate and it is difficult to obtain small-sized PtCo alloys, and to provide a PtCo ordered alloy material and its preparation method and application. The PtCo ordered alloy material obtained by the preparation method of the present invention has a small size, a high utilization rate of precious metals and good catalytic performance.
[0005] In a first aspect, the present invention provides a method for preparing a PtCo ordered alloy material; the method comprises the following steps:
[0006] S1. Defecting the carbon precursor under an active atmosphere to obtain a porous carbon support; the active atmosphere is selected from any one of ammonia, carbon dioxide and water vapor;
[0007] S2. subjecting a mixture of a platinum source, a cobalt source, the porous carbon support and a polyol to a microwave reaction to obtain a PtCo disordered alloy;
[0008] S3. Heat-treating the PtCo disordered alloy in a protective atmosphere to obtain the PtCo ordered alloy material.
[0009] In the present invention, when the active atmosphere is ammonia, N-doped carbon defects are mainly introduced, and when the active atmosphere is carbon dioxide or water vapor, carbon intrinsic structural defects are mainly generated, including topological defects and vacancy defect structures.
[0010] In the present invention, the purpose of the defect treatment is to use active atmosphere to react chemically with carbon atoms at high temperature to achieve etching of carbon powder particles, thereby forming a porous carbon carrier (DXC) with rich defects of different types. It will also have the function of pore making, and produce a large number of mesoporous structures on the surface of carbon particles; because the original carbon six-membered ring is destroyed, the local electron cloud density of carbon atoms is significantly different, such as after N doping, because the electronegativity of N atoms is greater than that of C atoms, electrons are attracted by N atoms, thereby causing the electron cloud density of C atoms to become low, and when the PtCo alloy particles are loaded at this site, the electronic interaction between defective carbon and PtCo changes, thereby affecting the different electronic structures of PtCo sites, and then affecting subsequent ORR catalytic activity. Similarly, carbon intrinsic defects are due to the formation of five-membered, seven-membered rings or carbon vacancies, and the delocalized π electrons of local carbon are broken and redistributed, and the work function of carbon changes significantly. After loading PtCo, different carrier-electron interactions will inevitably occur, thereby realizing the regulation of PtCo electrocatalytic performance.
[0011] In addition, the porous structure produced by thermal etching of the carbon precursor can inhibit the agglomeration and growth of PtCo alloy particles during the high-temperature transformation of alloy ordering. In addition, the defective carbon will also inhibit the migration of particles at high temperatures due to the stronger binding energy between it and PtCo.
[0012] In the present invention, the carbon precursor may be a substance commonly used in the art, preferably carbon black.
[0013] In some specific embodiments, the carbon precursor is selected from one or more of XC-72R, KB-600 and EC-300.
[0014] In step S1, the temperature of the defect treatment may be 500°C-1100°C.
[0015] In some specific embodiments, in step S1, the temperature of the defect treatment is 400°C, 900°C or 1200°C.
[0016] In step S1, the defect treatment time may be 0.5-3 hours, for example, 1 hour.
[0017] In step S1, the temperature increase and decrease process of the defect treatment can be performed under an inert atmosphere, and the inert atmosphere is preferably argon.
[0018] In the present invention, the platinum source can be a conventional platinum-containing compound in the art, preferably a platinum salt, such as H 2 PtCl 6 or K 2 PtCl 4 .
[0019] In the present invention, the cobalt source may be a conventional cobalt-containing compound in the art, preferably a cobalt salt, such as CoCl 2 、Co(NO 3 ) 2 or Co(Ac) 2 .
[0020] In step S2, the molar ratio of the Pt element in the platinum source to the Co element in the cobalt source is 1:(1.1-1.5), for example, 1:1.25 or 1:1.27.
[0021] In step S2, the mass ratio of the total mass of the Pt element in the platinum source and the Co element in the cobalt source to the porous carbon support is less than 1:1.
[0022] In step S2, the polyol may be an alcohol substance commonly used in the art, preferably ethylene glycol.
[0023] In step S2, the temperature of the microwave reaction is preferably 120-190° C. The purpose of the microwave reaction is to cause the platinum source and the cobalt source to undergo a reduction reaction to perform alloying.
[0024] In some specific embodiments, in step S2, the temperature of the microwave reaction is 100°C, 180°C or 200°C.
[0025] In step S2, the microwave reaction time can be conventionally used in the art, preferably 5-30 min, such as 10 min.
[0026] In step S2, after the microwave reaction is completed, centrifugation, washing and drying are further performed; the number of washing is preferably 3 times, and the washing method is preferably water washing; the drying method is preferably vacuum drying, and the drying time is preferably 12 hours.
[0027] In step S3, the temperature of the heat treatment is preferably 550-800°C, for example 700°C.
[0028] In step S3, the heating rate of the heat treatment may be conventional in the art, preferably 2-5°C / min, such as 5°C / min.
[0029] In step S3, the heat treatment time is preferably 0.5-8 hours, for example 2 hours.
[0030] In step S3, the protective atmosphere may be a gas conventionally used in the art, and may optionally be a mixture of hydrogen and argon.
[0031] In step S3, after the heat treatment, washing and drying are generally performed, and the washing preferably includes acid washing and water washing.
[0032] The pickling is preferably carried out using sulfuric acid or perchloric acid, and the concentration of the acid used in the pickling is preferably 0.1-0.5 mol / L.
[0033] The pickling temperature is preferably 40-80°C, such as 60°C.
[0034] The pickling time is preferably 4-12 hours, for example 6 hours.
[0035] Wherein, the number of times of water washing is preferably 3 times.
[0036] In a second aspect, the present invention provides a PtCo ordered alloy material, which is prepared by the preparation method as described above.
[0037] In a third aspect, the present invention provides an application of the aforementioned PtCo ordered alloy material as a catalyst in the field of fuel cells.
[0038] On the basis of being in accordance with the common sense in the art, the above-mentioned preferred conditions can be arbitrarily combined to obtain the preferred embodiments of the present invention.
[0039] The reagents and raw materials used in the present invention are commercially available.
[0040] The positive and progressive effects of the present invention are:
[0041] (1) The preparation method provided by the present invention utilizes active atmosphere assisted high temperature etching technology to prepare a porous carbon carrier rich in intrinsic defects. At high temperature, the strong binding energy between carbon defects and PtCo particles is used to achieve high temperature anchoring of small particles and inhibit particle agglomeration during the high temperature ordering transformation process, thereby preparing a small-sized PtCo ordered alloy material with an ordered alloy structure.
[0042] (2) The present invention achieves controllable regulation of the electronic structure of the active center of the PtCo alloy by changing different types of carbon defects, further optimizes the adsorption energy of ordered PtCo for oxygen intermediates, achieves a dual improvement in activity and durability, and ultimately achieves the purpose of reducing the amount of precious metals used. BRIEF DESCRIPTION OF THE DRAWINGS
[0043] Figure 1 This is the TEM image of the PtCo ordered alloy material prepared in Example 1.
[0044] Figure 2 This is an atomic-level resolution electron microscope image of the PtCo ordered alloy material prepared in Example 1.
[0045] Figure 3 This is the atomic arrangement diagram of the PtCo ordered alloy material prepared in Example 1.
[0046] Figure 4 This is a statistical diagram of the particle size of the PtCo ordered alloy material prepared in Example 1.
[0047] Figure 5 It is a comparison diagram of polarization curves of the PtCo ordered alloy materials of Example 1 and Comparative Example 1.
[0048] Figure 6 This is a comparison diagram of the polarization curves of the PtCo ordered alloy materials prepared in Examples 1-3. DETAILED DESCRIPTION
[0049] The present invention is further described below by way of examples, but the present invention is not limited to the scope of the examples. The experimental methods in the following examples without specifying specific conditions are carried out according to conventional methods and conditions, or selected according to the product specifications.
[0050] Example 1
[0051] (1) Weigh 500 mg of XC-72R as a carbon precursor, place it in a tube furnace, evacuate it, and then introduce NH 3 The defect treatment process of the carbon precursor was carried out as an active atmosphere, and the defect treatment parameters were set as follows: heating rate 5°C / min, defect treatment time 1h, heating / cooling protective atmosphere was Ar, defect treatment temperature 900°C; after natural cooling, the etched porous carbon support was taken out and recorded as NC;
[0052] (2) First, weigh 409.81 mg of H 2 PtCl 6 6H 2 O, 129.8 mg CoCl 2 and 262 mg of NC prepared in step (1), dissolved in 200 mL of ethylene glycol solution, and after fully dissolved, placed in a microwave reactor, and set the microwave reaction temperature to 180° C. and the microwave reaction time to 10 minutes; after the reaction, the product was centrifuged, washed three times with water, and placed in a vacuum oven for 12 hours to obtain a PtCo disordered alloy, recorded as PtCo / NC;
[0053] (3) Take 100 mg of PtCo / NC prepared in step (2) and place it in a high-temperature tube furnace for heat treatment. The heat treatment parameters are set as follows: heating rate 5°C / min, heat treatment time 2h, protective atmosphere 10% H 2 -90% Ar mixed gas, heat treatment temperature is 700℃;
[0054] After the heat treatment, the powder was taken out and cooled naturally. 2 SO 4 The mixture was washed and stirred in the solution for 6 hours at a temperature of 60°C, and then filtered and washed with ultrapure water for 3 times. The mixture was placed in a vacuum drying oven for 12 hours to obtain a PtCo ordered alloy material, which was recorded as O-PtCo / NC catalyst.
[0055] Example 2
[0056] The difference from Example 1 is that the active atmosphere in step (1) is CO 2 , and the PtCo ordered alloy material is obtained, denoted as O-PtCo / CO 2 -C catalyst.
[0057] Example 3
[0058] The difference from Example 1 is that the active atmosphere in step (1) is H 2 O, and the PtCo ordered alloy material is obtained, which is recorded as O-PtCo / H 2 OC catalyst.
[0059] Example 4
[0060] The difference from Example 1 is that the temperature of defect treatment is 400°C, which is recorded as O-PtCo / NC-400°C catalyst.
[0061] Example 5
[0062] The difference from Example 1 is that the temperature of the defect formation treatment is 1200°C.
[0063] Example 6
[0064] The difference from Example 1 is that the temperature of the microwave reaction is 100°C
[0065] Example 7
[0066] The difference from Example 1 is that the temperature of the microwave reaction is 200°C
[0067] Comparative Example 1
[0068] The commercial Pt / C catalyst is a 20% Pt / C catalyst purchased from JM.
[0069] Comparative Example 2
[0070] Compared with Example 1, the only difference is that sodium borohydride reduction method is used in step 2, specifically:
[0071] First, weigh 409.81 mg of H 2 PtCl 6 6H 2 O, 129.8 mg CoCl 2 and 262mg steps (1) The prepared NC was dissolved in 200 mL of aqueous solution. After it was fully dissolved, 10 mg of sodium borohydride was added and placed in a microwave reactor. The microwave reaction temperature was set to 120° C. and the microwave reaction time was 10 min. After the reaction was completed, the product was centrifuged, washed three times with water, and placed in a vacuum oven for 12 hours to obtain a PtCo disordered alloy, which was recorded as PtCo / NC.
[0072] Comparative Example 3
[0073] Compared with Example 1, the only difference is that in step 2, a platinum source is first added, microwave reaction is performed for 5 minutes, and then a cobalt source is added, and microwave reaction is performed for another 10 minutes.
[0074] Effect Example
[0075] 2 mg of the PtCo ordered alloy material prepared in the embodiment or comparative example was weighed, 1 mL of isopropanol, 950 mL of water and 50 μL of 5% Nafion solution were added to prepare 2 mL of a dispersion with a concentration of 1 mg / mL. After ultrasonic dispersion for 2 hours, it was dropped onto a previously polished and washed glassy carbon (GC, 5 mm) electrode, and the catalyst loading was controlled at 15 μg / cm 2 ; Then, using a three-electrode system, in 0.1 M HClO 4 Electrochemical ORR tests were carried out in solution.
[0076] Implementation Particle size / nm Half-wave potential / V Example 1 4.8nm 0.885 Example 2 5.4nm 0.871 Example 3 6.3nm 0.860 Example 4 6.7nm 0.864 Example 5 4.5nm 0.878 Example 6 5.3nm 0.872 Example 7 7.5nm 0.867 Comparative Example 1 2.5nm 0.850 Comparative Example 2 8nm 0.842 Comparative Example 3 6.9nm 0.856
[0077] The preparation method provided by the present invention realizes controllable regulation of the electronic structure of the active center of the PtCo ordered alloy material by changing different types of carbon defects, thereby improving the utilization rate of the precious metal. The prepared PtCo ordered alloy material has a higher half-wave potential and exhibits better catalytic activity.
[0078] Figure 1-Figure 3 The microstructure of the PtCo ordered alloy material obtained in Example 1 is shown in FIG. Figure 1 This is a TEM image, from which it can be seen that in the PtCo ordered alloy material prepared in the present invention, the PtCo alloy is uniformly distributed on the porous carbon support. Figure 2 This is an atomic-level resolution electron microscope image. Figure 3 for Figure 2 From the local enlarged view, it can be seen that Pt atoms and Co atoms are arranged in order. Figure 4This is a particle size distribution diagram of the PtCo ordered alloy material prepared in Example 1. It can be seen that the concentration of the normal distribution of the particle size of the prepared material is high, its size distribution is uniform, and the size is small.
[0079] Figure 5 The polarization curve comparison diagram of the PtCo ordered alloy material of Example 1 and Comparative Example 1. Figure 1 As can be seen from Table 1, the half-wave potential of oxygen reduction (ORR) of O-PtCo / NC catalyst is significantly higher than that of commercial Pt / C, showing better catalytic activity.
[0080] Figure 6 The polarization curve comparison diagram of the PtCo ordered alloy material obtained in Examples 1-3 is shown in FIG. Figure 2 As can be seen from Table 1, the ORR activity order is O-PtCo / NC>O-PtCo / CO 2 -C>O-PtCo / H 2 OC, and the activity is higher than that of commercial Pt / C, showing good application prospects.
[0081] The embodiments described above are only some embodiments of the present invention, which are convenient for those skilled in the art to understand and use the present invention. Obviously, any person skilled in the art can slightly modify or change the present embodiment and apply it to other embodiments without creative work. Therefore, the present invention is not limited to the above embodiments, and any equal changes, simple modifications and modifications made within the scope of the present invention still belong to the scope of the present invention.
Claims
1. A method for preparing a PtCo ordered alloy material, characterized in that: It includes the following steps: S1. Defecting the carbon precursor under an active atmosphere to obtain a porous carbon support; the active atmosphere is selected from any one of ammonia, carbon dioxide and water vapor; S2. subjecting a mixture of a platinum source, a cobalt source, the porous carbon support and a polyol to a microwave reaction to obtain a PtCo disordered alloy; S3. Heat-treating the PtCo disordered alloy in a protective atmosphere to obtain the PtCo ordered alloy material.
2. The method for preparing the PtCo ordered alloy material according to claim 1, characterized in that: In step S1, the temperature of the defect treatment is 500°C-1100°C; And / or, in step S2, the temperature of the microwave reaction is 120-190°C; And / or, in step S3, the temperature of the heat treatment is 550-800°C.
3. The method for preparing the PtCo ordered alloy material according to claim 1, characterized in that: In step S1, the temperature of the defect treatment is 400°C, 900°C or 1200°C; and / or, the temperature of the microwave reaction is 100° C., 180° C. or 200° C.; And / or, in step S3, the temperature of the heat treatment is 700°C.
4. The method for preparing the PtCo ordered alloy material according to claim 1, characterized in that: The carbon precursor is carbon black, and the carbon black is preferably one or more selected from XC-72R, KB-600 and EC-300; And / or, the platinum source is a platinum salt, such as H2PtCl6 or K2PtCl4; and / or, the cobalt source is a cobalt salt, such as CoCl2, Co(NO3)2 or Co(Ac)2; And / or, the polyol is ethylene glycol.
5. The method for preparing the PtCo ordered alloy material according to claim 1, characterized in that: The molar ratio of the Pt element in the platinum source to the Co element in the cobalt source is 1:(1.1-1.5), for example, 1:1.25 or 1:1.27; And / or, in step S2, the mass ratio of the total mass of the Pt element in the platinum source and the Co element in the cobalt source to the porous carbon support is less than 1:
1.
6. The method for preparing the PtCo ordered alloy material according to claim 1, characterized in that: In step S1, the defect treatment time is 0.5-3h, for example, 1h; And / or, in step S2, the microwave reaction time is 5-30 min, for example 10 min; And / or, in step S3, the heat treatment time is preferably 0.5-8h, for example 2h.
7. The method for preparing the PtCo ordered alloy material according to claim 1, characterized in that: In step S1, the temperature increase and decrease process of the defect treatment is carried out under an inert atmosphere, and the inert atmosphere is preferably argon; And / or, in step S2, after the microwave reaction is completed, centrifugation, washing and drying are further performed; the number of washing is preferably 3 times, and the washing method is preferably water washing; the drying method is preferably vacuum drying, and the drying time is preferably 12 hours.
8. The method for preparing the PtCo ordered alloy material according to claim 1, characterized in that: In step S3, the heating rate of the heat treatment is 2-5°C / min, for example, 5°C / min; And / or, in step S3, the protective atmosphere is a mixture of hydrogen and argon, for example, a mixture of 10% hydrogen and 90% argon; And / or, in step S3, after the heat treatment, washing and drying are also performed; the washing preferably includes acid washing and water washing; wherein, the acid washing is preferably performed with sulfuric acid or perchloric acid, and the concentration of the acid used in the acid washing is preferably 0.1-0.5 mol / L; the temperature of the acid washing is preferably 40-80°C, for example 60°C; the time of the acid washing is preferably 4-12h, for example 6h; the number of water washings is preferably 3 times.
9. A PtCo ordered alloy material, characterized in that: The method is prepared according to any one of claims 1 to 8.
10. Use of the PtCo ordered alloy material as claimed in claim 9 as a catalyst in the field of fuel cells.
Citation Information
Cited By
PtCo intermetallic compound based on microwave-assisted gas phase dispersion method and preparation method of PtCo intermetallic compound
CN122091620A
